2022
DOI: 10.1128/mra.00094-22
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Transferable Linear Plasmid Carrying the Macrolide-Clindamycin Resistance Gene erm (X) in a Cutibacterium acnes Isolate from a Patient with Acne Vulgaris in Japan

Abstract: Cutibacterium acnes , one of the common skin bacteria, is known to exacerbate acne vulgaris. Macrolide-clindamycin-resistant C. acnes strains have been reported worldwide. In this study, we found a transferable linear plasmid carrying the macrolide-clindamycin resistance gene erm (X) in a C. acnes strain isolated from a patient with acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, two recent studies have reported the antimicrobial resistance of C. avidum . One study reported that erm(X) can be transmitted between C. acnes and C. avidum via Tn5432, which leads to both macrolide and clindamycin resistance [ 25 ]. Another study reported that a C. avidum strain acquired resistance to rifampin and levofloxacin during the treatment of orthopedic device-related infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent studies have reported the antimicrobial resistance of C. avidum . One study reported that erm(X) can be transmitted between C. acnes and C. avidum via Tn5432, which leads to both macrolide and clindamycin resistance [ 25 ]. Another study reported that a C. avidum strain acquired resistance to rifampin and levofloxacin during the treatment of orthopedic device-related infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…qPCR was performed to determine the copy number of pTZC1. Genomic DNA was extracted as previously described ( 15 ). The copy number was analyzed using real-time PCR and Thunderbird SYBR qPCR Mix (Toyobo, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in 23S rRNA and acquisition of ribosomal methylase coding genes erm (X) and erm (50) are well-known mechanisms of resistance against the macrolides-clindamycin ( 12 , 13 ). erm (X) is found on chromosomes or linear plasmids and is transmitted between C. acnes strains ( 14 , 15 ). In contrast, erm (50) and the tetracycline resistance gene tet (W) are only found in C. acnes and are located on pTZC1.…”
Section: Introductionmentioning
confidence: 99%
“…As a breakpoint is not listed for Pandoraea species, it’s for B. cepacia were used. Genomic DNA was extracted from a single colony on MHA using phenol-chloroform-isoamyl alcohol (25:24:1) as previously described ( 5 ). Whole-genome sequencing was performed using Sequel IIe (Pacific Biosciences [PacBio], USA).…”
Section: Announcementmentioning
confidence: 99%